Central America Social Expenditures and Institutional Review : Nicaragua - World Bank (World Bank, Washington, DC, 2016)
Nicaragua has had decent economic growth in the past decade, which has contributed to substantial poverty reduction (the largest in Central America), as well as improvements in human development indicators. Fiscal accounts have deteriorated recently, which may pose some challenges to the sustainability of current levels of financing for social sector expenditures. Better planning and monitoring of social spending are needed to improve Nicaragua’s budget management. While Nicaragua has a medium-term development plan, the use of results-oriented budget formulation is still in its early stages. Low and inefficient public spending in education, coupled with outdated legal and institutional frameworks and high dropout rates present are significant barriers to increasing enrollment and providing quality education. Progress in key areas such as child and maternal mortality, but lowest per capita health spending in Central America, as well as institutional and governance challenges limit coverage and quality of services. There is need for increased spending in social assistance interventions, better coordination among implementing agencies, and revised targeting to ensure decent coverage of programs among the poorest. Government policies also reflect the need for improved controls and implement social audits, which are considered a pillar of participatory governance. However, these still need to be implemented on a broader scale and publicly disseminated.